Does inequality affect redistribution? The political economy aspect of the redistribution puzzle - Zabel, Arecida Sophia Hildegard (2018)
The relationship between income inequality and the level of redistribution seems to be clear only at first glance. Despite the positive relation proposed by theory, empirical results remain ambiguous. The work project “Does Inequality Affect Redistribution? The Political Economy Aspect of the Redistribution Puzzle” seeks to investigate the channels that affect the relationship between inequality and redistribution. Using a TSCS data set on absolute redistribution in 64 countries starting in 1975, country fixed effects regressions yield that evidence for a positive relationship is weak. Furthermore, dependence on political-economy factors seems to be of importance and should be subject to further investigations.